“That They May Be One”: The Challenge to Be Part of an Affirmative Answer to the Prayer of Jesus As Recorded in John Seventeen - Thomas Sibley (Kairos (English Ed.), 2008)
The article is an exposition of John 17 which provides the most detailed expression of Jesus’ desire for his followers. As he faces the hour of the redemptive event, Jesus prays for not only for himself and his closest disciples, but for all who will become believers through the message of the Apostles. The exposition identifies the subjects of Christ’s prayer, the requests themselves, and the purpose of the requests. The purpose is identified as “that the world may know that the Son is sent from the Father and that the Father loves the disciples as he loves the Son.” Implications are drawn from the prayer for believers living in a post-modern culture.